Analiza zależności pomiędzy strukturą i funkcją produktów proteolitycznego procesowania Nukleobindyny-2 - Lenda, Rafał (Analysis of the Relationship Between the Structure and Function of Products of Proteolytic Processing of Nucleobindin-2, 2024)
Nesfatin-1 (N1), -2 (N2), and -1/2 (N1/2) are products of the proteolytical processing of the N-terminus of Nucleobindin-2 by prohormone convertases (PCs). Nucb2 and/or N1 (Nucb2/N1) are proteins involved in various functions, including energy homeostasis, stress responses, carcinogenesis, psycho-neuronal disorders, and blood pressure regulation. However, there are limited reports on the relationship between the structure and function of Nucb2/N1 and the purpose of the remaining nesfatins. These studies are crucial due to the multifunctional nature of Nucb2/nesfatins, their widespread expression, and their potential medical applications. Additionally, examining the structural differences between nesfatin homologs and their interactions with ligands may reveal species-specific functions of the peptides. Five nesfatin homologs from two species were purified, including human N1, N2, N1/2, and chicken N1, and N1/2. Comprehensive structural analysis of nesfatins and their interactions with divalent metal cations were conducted. This is the first and only analysis of this type available in the literature. The results showed conservation of the highly disordered structure between human and chicken homologs of apo-N1, both displaying elongated and ellipsoidal shapes. The structure of apo-N1/2 homologs was revealed as mosaic with intertwined ordered and disordered regions and extended shape. The N2 fragment's structural role was suggested based on the data. Moreover, the N2 fragment in the context of the N1 fragment (N1/2) induced different molecular properties, not a simple sum of the isolated fragments' effects. Thus, proteolytical processing of Nucb2/N1/2 may act as an activation mechanism, enabling N1 to interact with multiple proteins. Zn(II) had a strong effect on the properties and conformation of nesfatins. Human and chicken homologs of holo-N1 underwent a disorder-to-order transition induced by Zn(II), associated with a decrease in hydrodynamic volume and strong protection of their backbone against H/D exchange in the M30 region. Dimerization of the peptides under Zn(II) treatment was also observed for holo-N1 homologs. Chicken holo-N1 was more prone to aggregation than the human homolog. Structurization and change in the oligomeric state of holo-N1 might be universal, facilitating interactions with different binding partners in vivo. Concealment of the anorexigenic core of neuropeptides might affect their function. Zn(II) binding by human and chicken holo-N1 homologs was associated with amyloid motif formation, indicating potential involvement in neurodegeneration processes. Zn(II) binding by hN2 and human and chicken N1/2 homologs resulted in strong destabilization of the proteins. Chicken N1/2 was more susceptible to oligomerization and aggregation under Zn(II) treatment. The interaction mode of chicken N1/2 with Zn(II) differed from the human homolog. Zn(II) induced strong exposition of the backbone of human and chicken N1/2 homologs, particularly in the M30 and PCs-recognition regions. Proteolytical processing of N1 precursors, their biological activity, and localization may be Zn(II)-dependent. The in-depth structural analysis of human and chicken nesfatin homologs provided new insights into the relationship between their structure and function, forming a basis for subsequent studies.
Keywords: Homo sapiens; Gallus gallus; Nukleobindyna-2; nesfatyna-1; nesfatyna-2; nesfatyna-1/2; hormon peptydowy; jony cynku; nucleobindin-2; nesfatin-1; nesfatin-2; nesfatin-1/2; hormone peptide; zinc ions